87Sr/86Sr ratios in shallow and deep aquifers and thermal water from the eastern boundary fault of the northern upper Rhine Graben at the Heidelberg Basin, Germany: 15th Water-Rock Interaction International Symposium, WRI-15 - Schmidt, Gerhard; Al Najem, Sami; Isenbeck-Schröter, Margot; Freundt, Florian; Kraml, Michael; Eichstädter, René; Aeschbach, Werner (Procedia earth and planetary science, 2017)
87Sr/86Sr ratios have been used as a tracer of fault-controlled fluid ascent into shallow aquifers at the Western Boundary Fault (WBF) of the northern upper Rhine Graben in Germany, a major rift system of the European continent. The 87Sr/86Sr ratios and Sr contents from the Quarternary groundwater conducting sediments of the uppermost aquifer increase with decreasing distance to the WBF. The 87Sr/86Sr ratios and Sr contents of the shallow groundwater range from 0.70877 to 0.71022 and 0.41 to 2.30 mg/l, respectively. The Strontium isotope ratios are important tracers of hydrological processes such as water-rock interaction and groundwater mixing at active faults and thus a powerful geochemical tool for the detection of the ascent of deep fluids at hydraulically active segments of faults and its mixing with shallow recharged groundwater.